Any Willing Provider: An Unacceptable Risk for a Marginal Gain (Hinckley Journal of Politics; Vol 7 (2006), 2017)
It is no secret that many Americans are less than happy with their health care coverage – either due to a total lack of coverage or simply a lack of choice and flexibility within their current plan. The latter objection is often a feature of the coverage afforded by Managed Care Organizations (MCOs), also commonly known as Health Maintenance Organizations (HMOs). These plans usually restrict a patient’s choice of doctors in exchange for lower monthly premiums. In response to frustrated patients and citizens, legislation titled Any Willing Provider has been introduced in several states, which aims to curb the ability of an HMO to control patient access to the healthcare market. While the goals of this type of legislation seem noble and logical on their face – allowing patients to have their choice of doctors and not allowing companies to restrict access to the market – the unintended consequences of these laws could easily outweigh their benefits. By undermining an HMO’s cost-saving techniques, America runs the risk of increasing the number of uninsured citizens. This report will outline the issues and debates surrounding the MCO/HMO industry in America as well as the Any Willing Provider movement. It will then argue that this kind of legislation, while desirable on its surface, demonstrates a potential for negative consequences, which may be too much of a risk to our healthcare system.